Evidence of innovation performance in the period of economic recovery in Europe - Makrevska disoska, Elena; Tevdovski, Dragan; Toshevska trpchevska, Katerina; Stojkoski, Viktor (Taylor and Francis Group, 2018)
This paper provides empirical evidence on the innovation performance in the European countries in the years of recovery from the global economic and financial crisis by using the CDM model of simultaneous equations. The model directly links R&D engagement and intensity to innovation outcomes measured either as process or as product innovation, and then estimates the effectiveness of the innovative efforts leading to productivity gains. The difference between the drivers of innovation systems and its influence over the productivity growth is analyzed between two different institutional settings in Europe. For that purpose a company-level dataset is used from the 2012 round of the Comunity Innovation Survey. Тhe results indicated that the recent financial crisis had negative influence on the companies’ willingness to innovate. The effect of the crisis led to further divergence in the innovation systems of these two institutional settings. Identifying the characteristics of the innovation systems and drivers of innovation during the turmoil shows that policy instruments on EU level should be oriented towards creation of competitive business environment, encouragement to adopt the best management techniques and organizational structures and improvement of well-functioning capital, product and labor markets.
Keywords: innovation; productivity; CDM model; European countries; economic recovery